2020
DOI: 10.1186/s12955-020-01494-x
|View full text |Cite|
|
Sign up to set email alerts
|

Health-related quality of life using specific and generic questionnaires in Spanish coeliac children

Abstract: Background We aimed to compare the perception of health-related quality of life (HRQOL) and related factors in Spanish coeliac children and their parents, using two questionnaires, the generic KIDSCREEN-52 and the specific the Celiac Disease DUX (CDDUX), and to assess the correlation between them. Methods Coeliac children, aged 8-18, who are members of the Madrid Coeliac Association (MCA) and their parents, answered the Spanish version of the CDDUX and KIDSCREEN-52 ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
2
5
0
1
Order By: Relevance
“…4,9,15,[17][18][19][20][21][22] Comparing the CDDUX total scores in children and adolescents, QoL appears to be neutral in Spanish, Dutch and Brazilian children with CD, while a good perception of QoL is found in Chileans, and a poor QoL is reported for Iranians and Moroccans. 5,9,17,[19][20][21][22] A similar comparison with the PedsQL in our study gave results comparable to those of Italian children with rheumatological diseases, 23 healthy children, 24 Argentinean and Canadian children with CD. 12,15 It is notable that compared to CDDUX scores of our study, the Argentinians reported higher scores (good), while Canadians scores were lower (low/neutral range).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…4,9,15,[17][18][19][20][21][22] Comparing the CDDUX total scores in children and adolescents, QoL appears to be neutral in Spanish, Dutch and Brazilian children with CD, while a good perception of QoL is found in Chileans, and a poor QoL is reported for Iranians and Moroccans. 5,9,17,[19][20][21][22] A similar comparison with the PedsQL in our study gave results comparable to those of Italian children with rheumatological diseases, 23 healthy children, 24 Argentinean and Canadian children with CD. 12,15 It is notable that compared to CDDUX scores of our study, the Argentinians reported higher scores (good), while Canadians scores were lower (low/neutral range).…”
Section: Discussionsupporting
confidence: 85%
“…Nonadherence may be associated with reduced patient growth, symptoms, and poorer quality of life (QoL) 2,3 . The need to follow a strict, restrictive, and permanent diet in coeliac patients may cause stigma and have a considerable negative impact on the health‐related QoL (HRQoL) of patients and their families 4,5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The health-related QOL for Saudi CD children on GFD was generally comparable to the healthy control, except for the general health domain [ 25 ]. A CD children study from Spanish revealed the main concerns of the respondents to the social and economic difficulties of GFD [ 26 ]. In Sweden, there was no clear relationship between CD and socioeconomic place [ 27 ].…”
Section: Suggested Causes For the Recent Increase In CD Incidencementioning
confidence: 99%
“…There are two main types, generic and specific questionnaires. Generic questionnaires measure the daily life aspects of HRQoL in patients who have several conditions, whereas specific questionnaires focus on specific aspects related to the disease and its treatment ( 11 ). Generic self-administered questionnaires are mostly used as indicators for HRQoL, including the EuroQol 5-Dimensions (EQ–5D) and Short Form-36 Health Survey (SF-36) ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%